PENGARUH CURRENT RATIO, RETURN ON ASSETS, DAN DEBT TO EQUITY RATIO TERHADAP HARGA SAHAM PT. INDOSAT Tbk PERIODE 2020-2024 - Andi Asrul; Mahadi Alkautsar; Muhammad Jovan Edliansyah; Fazhar Sumantri (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2025)
This research was carried out to examine the extent to which the stock price of PT. Indosat, Tbk is influenced by CR, ROA, and DER. The quantitative approach was chosen as the research methodology, and the current research uses secondary data types. The data samples analyzed include quarterly data of the company PT. Indosat, Tbk from 2020 to 2024 and information from Yahoo Finance about stock prices. Results from the T-test analysis indicate that the stock price of PT. Indosat, Tbk is impacted by DER. Conversely, the stock price of PT. Indosat, Tbk is not influenced by ROA and CR. In the F-test evaluation, the stock value of PT. Indosat, Tbk is not affected by CR, ROA, and DER.